Patients' experiences of early postoperative cognition and its relation to cognitive decline and inflammatory responses: a protocol for a mixed-methods study. Issue 12 (15th December 2019) - Nilsson, Ulrica; Liander, Karin; Rooyackers, Olav; Eriksson, Lars I
Abstract : Introduction: In the early weeks after surgery, patients may experience cognitive changes and impaired memory and concentration—changes commonly referred to as postoperative cognitive decline. It is often the patient and/or a relative that initially detects a change in cognitive capacity after surgery, typically when resuming daily activities. We lack information about how patients experience early postoperative cognition ( delayed neurocognitive recovery ) and if these experiences can be reflected in biochemical pattern of inflammatory signalling molecules, cognitive function as well as on quality of postoperative recovery. Methods and analysis: The study has a mixed-methods design that is integration of qualitative and quantitative data within a single investigation. Participants included will be patients aged ≥60 years that are undergoing major elective joint replacement surgery (n=40) and their relative. Patient's experience of his/her early cognition will be captured by interviews on postoperative day 13–16 during the follow-up visit. A relative will also be interviewed on the same day or the day after. Cognitive function will be measured preoperatively and on postoperative day 13–16 using the International Study Group of Postoperative Cognitive Dysfunction test battery. Symptoms/discomfort will be measured preoperatively and postoperatively (on postoperative day 1 and 2 and at the follow-up visit day 13–16) by the Swedish version of Quality of Recovery and by a visual analogue scale assessing pain intensity. Biomarkers will also be collected at the same time points. The findings from the interviews will be sorted out depending on group stratification (no delayed neurocognitive recovery and delayed neurocognitive recovery). The qualitative and quantitative findings will be compared to seek for similarities and differences. Ethics and dissemination: The project has been approved by the Swedish Ethical Review Authority (2019–02968) and will follow the principles outlined in the 1964 Helsinki Declaration and its later amendments. Results from this study will be disseminated in peer-reviewed journals, scientific conferences and in social media.